The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/v10100566
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on High-Throughput Sequencing (HTS) for Adventitious Virus Detection: Upstream Sample Processing and Library Preparation

Abstract: A key step for broad viral detection using high-throughput sequencing (HTS) is optimizing the sample preparation strategy for extracting viral-specific nucleic acids since viral genomes are diverse: They can be single-stranded or double-stranded RNA or DNA, and can vary from a few thousand bases to over millions of bases, which might introduce biases during nucleic acid extraction. In addition, viral particles can be enveloped or non-enveloped with variable resistance to pre-treatment, which may influence thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…High-throughput sequencing (HTS) is a non-specific technique with the potential to detect both known and unknown adventitious agents including viruses 7,[14][15][16][17] . High-throughput molecular biology methods (HTS combined with a pan-viral microarray) had succeeded in detecting the contamination of Rotarix vaccine by a porcine circovirus 18 .…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput sequencing (HTS) is a non-specific technique with the potential to detect both known and unknown adventitious agents including viruses 7,[14][15][16][17] . High-throughput molecular biology methods (HTS combined with a pan-viral microarray) had succeeded in detecting the contamination of Rotarix vaccine by a porcine circovirus 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Following RNA extraction and viral RNA enrichment from the host RNA (Forth and Hoper, 2019;Houldcroft et al, 2017;Sathiamoorthy et al, 2018;Singanallur et al, 2019), the first critical quality control (QC) step (Fig. 2) is to test both quantity and integrity of the starting viral RNA (Hauck et al, 2018;Ng et al, 2018;Yang et al, 2016). The necessity to control virus tire or genome copy numbers in comparative studies has been demonstrated in several studies as false positive variant calls become more evident with lower material inputs (Gallet et al, 2017;Illingworth et al, 2017;McCrone and Lauring, 2016).…”
Section: Sample and Library Preparationmentioning
confidence: 99%
“…High background from cellular nucleic acids will reduce the sensitivity of HTS virus detection [ 13 , 14 ]. In most cases, the cellular nucleic acids are the most crucial factor for influencing the sensitivity of virus detection, since they typically dominate the viral read number [ 11 , 15 , 16 ]. Reducing the cellular nucleic acid, such as by nuclease treatment prior to sequencing, may enhance the sensitivity of virus detection in downstream bioinformatics analysis.…”
Section: Factors Influencing Sensitivity Of Virus Detectionmentioning
confidence: 99%
“…As shown in Figure 1 (closed circles), without incorporation of steps to reduce the background, even an entire Illumina HiSeq flow cell run, generating 2.5 × 10 9 reads in a paired-end mode (for example 2 × 100 bp) would not likely produce a single PCV read below a sensitivity of 1 × 10 4 genomes/mL. While mechanisms of target enrichment and background removal are beyond the scope of this paper [ 11 ], when we explore the effect of improving this signal-to-noise ratio (S/N) by 1000× ( Figure 1 , closed squares), similar levels of sensitivity could then be obtained using a more modest platform (MiSeq, ~1.2 × 10 7 paired-end reads).…”
Section: Factors Influencing Sensitivity Of Virus Detectionmentioning
confidence: 99%
See 1 more Smart Citation